IMPLEMENTASI KEGIATAN JURNAL LITERASI DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA SD - Lutfia Lestari; Lina Putriyanti; Qoriati Mushafanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The background of this research is the low interest and reading ability of students, as reflected by the minimal visits to the library and reading corners, as well as the lack of reading habits both at school and at home. To address this problem, this study aims to examine and analyze the implementation of literacy journal activities in improving the reading skills of elementary school students and to identify and analyze the impact of these literacy journal activities. This research uses a qualitative descriptive approach, employing data collection techniques such as observation, interviews, questionnaires, and documentation. The validity of the data is strengthened through triangulation techniques and analyzed using the Miles and Huberman model, which includes data collection, data reduction, data display, and drawing conclusions. The results show that literacy journal activities significantly improve students’ reading abilities, as evidenced by an 88.89% literacy achievement in the educational report. Besides the improvement in reading skills, these activities also have a positive impact on increasing students’ interest in reading, enhancing their self-confidence, and strengthening the involvement of parents and teachers in supporting the students’ learning process. Thus, literacy journal activities are proven to be effective and are recommended to be implemented sustainably as a strategy to improve the literacy culture in elementary schools.